The Business of Emotions - Soni, Divya (Indian Journal of Marketing, 2012)
This article introduces its readers to the new wave of emotional branding. It throws light on the concept of emotional branding and the reasons of its increasing popularity. It discusses the power of emotions over rationality. Emotional branding in Indian scenario is illustrated by discussing latest emotional advertisements. Finally, the article suggests the companies, marketers and customers on what should they expect from this new trend of emotional branding.